High fibroblast activation protein expression in hepatocellular carcinoma: CT imaging features and histological characteristics - Wang, Tian-Cheng; Huang, Wei; Li, Shu-Xian; Li, Jun-Xiang; Zhou, Peng; Wang, Li-Zhou; Wei, Nan; Cai, Wen-Wu; Hu, Jun-Jiao; Xiao, Yu-Dong (Academic radiology, 2025)
Rationale and Objectives - To clarify computed tomography (CT) imaging features of high fibroblast activation protein (FAP) expression in hepatocellular carcinoma (HCC) and to investigate their correlation to histological characteristics and prognosis. - Methods - This retrospective multicenter study evaluated patients with HCC who underwent liver resection between August 2013 and June 2023. Histological staining for FAP was performed, and patients were classified into low and high-FAP expression groups. A predictive model was developed and validated to identify FAP expression levels among CT imaging features. Moreover, CT imaging-related histological characteristics were evaluated. With the predictive model, patients in training cohort were stratified into predicted low and high-FAP expression groups. Overall survival (OS) and recurrence-free survival (RFS) were compared accordingly. Besides, propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) analysis were performed, and OS and RFS between the two groups were also compared. - Results - In total, 1197 patients were included (high-FAP HCCs, n=267). Delayed central enhancement (OR: 15.196, 95% CI: 8.996-25.670, P<0.001) and dilated vasculature (OR: 7.455, 95% CI: 4.928-11.277, P<0.001) independently predicted high-FAP expression (AUCs: 0.779, training; 0.766, external validation). Based on these two CT imaging features, intratumoral fibrosis (ITF) and vessel-encapsulating tumor cluster (VETC) pattern were determined. Compared to low-FAP HCCs, high-FAP HCCs were more frequently with high ITF grade (54.7% vs. 22.4%; P<0.001) and VETC pattern (52.1% vs. 22.6%; P<0.001). Patients were divided into predicted low (n=564) and high (n=262) FAP expression groups. The predicted low-FAP group had significantly better or favorable trend toward improved OS and RFS than predicted high-FAP group before (P<0.001, OS and RFS), and after PSM (P=0.009, OS; P=0.005, RFS) and IPTW (P=0.019, OS; P=0.077, RFS). - Conclusion - Delayed central enhancement and dilated vasculature are independent factors of high-FAP expression in HCC. Noninvasive identifying FAP expression may offer potential prognostic and therapeutic insights.